A hybrid simulation-based approach for optimizing building envelope design with natural stones: Enhancing sustainable energy efficiency and material integration - Balo, Figen; Ari, Ilknur; Yigit, Aziz (Taylor & Francis Inc, 2025)
This study addresses this gap by systematically evaluating how regionally sourced natural stones, combined with modern insulation and structural materials, can optimize energy efficiency and reduce environmental impact in restaurant buildings, a high-energy-use building type. It is investigated 120 facade configurations for an Autodesk Revit-designed restaurant in Ankara, combining 10 natural stone cladding materials, 2 insulation materials, and 2 structural materials. Using IES-VE, annual energy consumption and CO2 emissions are simulated for each case, identifying the most efficient combinations. Regression analysis and sensitivity assessments quantify predictive relationships, while four Multi-Attribute Decision Analysis (MADA) methods cross-validate material rankings. Finally, Homer Pro evaluates renewable energy feasibility using site-specific meteorological data. Results demonstrate that optimal material selection reduces annual energy use by up to 2.4% (Delta 500 kWh) compared to worst-performing combinations, equivalent to 225 kg CO2 savings per building annually. MADA methods consistently rank Desert Yellow highest due to its low thermal conductivity and density. Renewable energy integration further enhances sustainability, with solar PV potential offsetting similar to 30% of operational energy demand. This work provides architects and policymakers with a replicable framework for sustainable facade design, bridging traditional materials with modern energy efficiency goals.
Keywords: Energy efficiency; natural stone cladding; sustainable construction; CO2 emissions; renewable energy integration